Distribution of decay-accelerating factor in the peripheral blood of normal individuals and patients with paroxysmal nocturnal hemoglobinuria (The Rockefeller University Press, 1985)
Decay-accelerating factor (DAF) is a 70,000 Mr protein that has been isolated from the membrane of red cells. The function of DAF is to inhibit the assembly of amplifying enzymes of the complement cascade on the cell surface, thereby protecting them from damage by autologous complement. We raised monoclonal antibodies to DAF and used them to study its distribution in cells from the peripheral blood of normal individuals and of patients with paroxysmal nocturnal hemoglobinuria (PNH), a disease characterized by the unusual susceptibility of red cells to the hemolytic activity of complement. The results of immunoradiometric assays and of fluorescence-activated cell sorter analysis showed that DAF was present not only on red cells but was widely distributed on the surface membrane of platelets, neutrophils, monocytes, and B and T lymphocytes. By Western blotting, we observed small but consistent differences in the Mr of DAF from the membranes of various cell types. Quantitative studies showed that phagocytes and B lymphocytes, which presumably enter more frequently in contact with immune complexes and other potential activators of complement, had the highest DAF levels. As previously reported by others, the red cells from PNH patients were DAF deficient. When the patients' red cells were incubated in acidified serum (Ham test), only the DAF-deficient cells were lysed. In addition, we detected defects in DAF expression on platelets and all types of leukocytes. The observed patterns of DAF deficiency in these patients were consistent with the concept that the PNH cells were of monoclonal origin. In one patient, abnormal and normal cells were found only in the erythroid, myeloid, and megakaryocytic lineages. In two other patients, the lymphocytes were also DAF deficient, suggesting that a mutation occurred in a totipotent stem cell. It appears, therefore, that the lesion leading to PNH can occur at various stages in the differentiation of hematopoietic cells.